2022
DOI: 10.1371/journal.pone.0273704
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of multi-site UK Biobank MRI brain phenotypes for the assessment of neuropsychiatric complications of SARS-CoV-2 infection: The COVID-CNS travelling heads study

Abstract: Introduction Magnetic resonance imaging (MRI) of the brain could be a key diagnostic and research tool for understanding the neuropsychiatric complications of COVID-19. For maximum impact, multi-modal MRI protocols will be needed to measure the effects of SARS-CoV-2 infection on the brain by diverse potentially pathogenic mechanisms, and with high reliability across multiple sites and scanner manufacturers. Here we describe the development of such a protocol, based upon the UK Biobank, and its validation with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…One limitation of this study is that data was collected at multiple centres and even though we used site as a nuisance regressor there might be unaccounted for non-linear effects. However Duff et al, 2022 showed that quantities derived from UK Biobank scans at different sites are reliable.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of this study is that data was collected at multiple centres and even though we used site as a nuisance regressor there might be unaccounted for non-linear effects. However Duff et al, 2022 showed that quantities derived from UK Biobank scans at different sites are reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Although structural scans, as utilised in this study, are not thought to suffer from degradation of image quality as a result of head motion to the same extent as other modalities, it is worth acknowledging that such confounds could increase the risk of false positives (37,38). However, this study aimed to address this by excluding scans with signi cant motion artefact (39). Finally, the analysis of recovery trajectories was underpowered which limits interpretation, but there was evidence of a trend towards recovery that continued into the second year.…”
Section: Discussionmentioning
confidence: 99%
“…3T MRI protocols were harmonised and the published standardised protocol was consistent across sites (39). Speci c brain regions were selected based on extant literature a priori to analysis; the parahippocampal gyrus, entorhinal cortex, orbitofrontal cortex, anterior cingulate cortex, insula and superior temporal gyrus (7,47,48,49,50,51).…”
Section: Neuroimagingmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, various tools and methods have been employed to evaluate OD in patients with COVID-19. For instance, Duff et al (2022) utilized brain magnetic resonance imaging (MRI) to assess the neuropsychiatric consequences of neocoronary pneumonia, demonstrating the high reliability of multiple imaging derived phenotypes (IDPs) in measuring the impact of SARS-CoV-2 infection on the brain through potential pathogenic mechanisms. Melkumyan et al (2022) conducted a cross-sectional study that analyzed the sensitivity to olfaction and trigeminal nerve-triggered olfaction, as well as the ability to distinguish between different odors, in patients recovering from neocoronary pneumonia and revealed pathological changes in olfactory and trigeminal perceptual abilities that result in OD.…”
Section: Assessment Of Odmentioning
confidence: 99%